Child retroperitoneal malignant teratoma at the Mother and Child University Hospital Lagune of Cotonou: about a case - GBENOU, ANTOINE SÉRAPHIN; FIOGBE, ARMAND MICHEL (My University, 2020)
Retroperitoneal malignant teratoma is a rare congenital tumor, representing 1%–10% of retroperitoneal tumors in children.It was a case of 3-year- old child, weighing 12 kg, without any particular history. Physical examination, found a swollen abdomen with collateral venous circulation, a voluminous mass occupying almost the entire abdominal cavity.Paraclinical examines (abdominal ultrasonography, abdominal CT) and macroscopic examination of surgical resected mass revealed a mixed tumor with solid tissue and cysts. The free offered chemotherapy was refused by the parents, the child was died two months later. Retroperitoneal malignant teratomas are rare tumors in children. In our case the diagnosis was late. Multidisciplinary treatment was handicapped by socio-economic factors.
Keywords: retroperitoneal malignant; teratoma; tumor; child; Cotonou.